Psychological Transitions of Children in the KKPK (Unusual Friends) through Maria Nikolajeva's Study - Ilmi, Aulia Fadzilatul; Indriyani , Jiphie Gilia (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study analyzes the psychological conflict of a child character in the story “Bukan Teman Biasa” (Not an Ordinary Friend) by Kirana Riris Santosa. The study focuses on the inner struggle of Rania, an elementary school student, who is caught between the demands of high academic achievement and the fundamental need for acceptance by her circle of friends. Using Maria Nikolajeva's children's literature theory, specifically the concepts of inner journey and power relationships, this qualitative study uses narrative analysis to explore the dynamics of the main character's identity formation. The results reveal that Rania's academic achievement, initially believed to be a source of self-esteem, actually turns into a trigger for social alienation. This situation forces Rania into an identity crisis, characterized by tension between her idealized self and her perceived self. This narrative represents the psychosocial complexity of children in a competitive education system. Practically, the findings of this study are expected to provide a reflection for educators and parents to create a more balanced educational approach that not only pursues cognitive achievement but also considers children's emotional and social well-being.